Biofuel production from waste cooking oil by catalytic reaction over Thai dolomite under atmospheric pressure: Effect of calcination temperatures - Chansiriwat, Wasipim; Chotwatcharanurak, Lalitphat; Khumta, Wanida; Suwannaruang, Totsaporn; Shahmoradi, Behzad; Kumsaen, Tinnakorn; Wantala, Kitirote (Engineering and Applied Science Research, 2021)
This study represented the catalytic pyrolysis of waste cooking oil (WCO) to produce biofuel via continuous reaction by using a pelleted Thai dolomite catalyst. The effect of calcination temperatures on catalyst synthesis was also examined in varying from 600 to 900°C for 2 h. Calcined Thai dolomite (CTD) samples were characterized by X-ray fluorescence spectrometer (XRF), thermo-gravimetric analysis (TGA) and differential-thermal analysis (DTA), X-ray diffractometer (XRD), N2 adsorption-desorption apparatus, and scanning electron microscope (SEM). In the catalytic pyrolysis process, the CTD catalysts were taken place in a packed bed pyrolysis reactor under atmospheric pressure for biofuel production in different reaction temperatures (450 to 550°C), and WHSV was about 0.5 h-1. The results were found that the effect of calcination temperature significantly altered the physicochemical properties of catalyst as well as the catalytic performance. The specific surface area and pore volume decreased with increasing the calcination temperatures. Besides, CaCO3 was transformed entirely into CaO at 900°C. For the catalytic pyrolysis process, the results were found that the highest pyrolytic yield was obtained at 500°C of reaction temperature using catalyst calcined at 700°C. Additionally, the results also expressed that the calcined temperature was significant in the quality of biofuel products. Moreover, the biofuel products can be separated into biogasoline, biokerosene, and biodiesel. The kinetic viscosity and heating value were satisfied following the standard values except for the acid value of all biofuel products. However, the acid value decreased when the CDT calcined at the highest temperature due to the obvious presenting of the CaO phase.